2017
DOI: 10.23986/afsci.63275
|View full text |Cite
|
Sign up to set email alerts
|

Electric energy consumption of milking process on some Finnish dairy farms

Abstract: The aim of this study was to examine the electric energy consumption of milking process on dairy farms and to evaluate the methods to improve the energy efficiency. The electricity consumption of the milking process was measured on three dairy farms in Southern Finland, and it varied between 37-62 Wh kg -1 milk. The largest energy saving potential was identified in milk cooling and the heating of cleaning water. Even simple methods, such as placing the condenser of the refrigeration system outside, may reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Milk cooling was found to be the second largest consumer of electricity (16.4 Wh kg −1 ) followed by water heating (3.2 Wh kg −1 ), and water pumping (2.6 Wh kg −1 ). All four studies [23,25,27,28] found milk harvesting to be the greatest consumer of electricity on AMS farms. Although none of the farms included in Table 4 are organic farms, electrical energy on organic farms is of greater importance compared to conventional farms because it represents 26% of total primary energy usage, compared to 17% on conventional farms (calculated using energy values in Table A1).…”
Section: Electrical Energymentioning
confidence: 99%
See 4 more Smart Citations
“…Milk cooling was found to be the second largest consumer of electricity (16.4 Wh kg −1 ) followed by water heating (3.2 Wh kg −1 ), and water pumping (2.6 Wh kg −1 ). All four studies [23,25,27,28] found milk harvesting to be the greatest consumer of electricity on AMS farms. Although none of the farms included in Table 4 are organic farms, electrical energy on organic farms is of greater importance compared to conventional farms because it represents 26% of total primary energy usage, compared to 17% on conventional farms (calculated using energy values in Table A1).…”
Section: Electrical Energymentioning
confidence: 99%
“…Similar to Upton et al [4] and Shine et al [8], Kraatz [22] found that milking equipment (vacuum pumps, milk bulk tanks, and water heaters) were the major electricity consumers on German dairy farms. In Finland, Rajaniemi et al [27] calculated electricity consumption associated with milk production (milk-cooling, milk harvesting and water-heating) to vary between 37 and 67 Wh kg m −1 when analyzing three dairy farms (mean herd size = 82 cows), one farm of which employed an AMS. Rajaniemi et al [27] reported milk harvesting and milk-cooling as the largest electricity consumers on the AMS farm, (29% and 22%, respectively), while on the two Conv-c farms, milk-cooling and water-heating were the two largest electricity consuming processes (22% and 16%, respectively).…”
Section: Electrical Energymentioning
confidence: 99%
See 3 more Smart Citations